Bibliometric Analysis: Sofware Usage Trends GeoGebra in Mathematics Learning From 2017 - 2022 - Rahmat Kusharyadi; Saffanah Pertiwi; Erika Yohanna Seventina Siahaan; Dadan Dasari (IKIP Mataram, 2023)
The use of GeoGebra Software in mathematics learning is the application of ICT-based learning that can be done in schools. This is done to make learning interactive. This study aims to determine and analyze trends in article writing with the theme of using GeoGebra software in mathematics learning between 2017-2022, articles, countries of origin, authors, and institutions that have the most citations and link strengths using databases. dimensions. The method used is bibliometric analysis. The sample used is 180 articles that were searched using the database dimensions according to the specified keywords. The data is stored in CSV format to be used in the VOSviewer software to obtain a mapping in search of publication trends. The trend of writing articles with the theme of using GeoGebra software experienced a significant increase between 2017 and 2021 by 279%. Analysis based on software VOSviewer has 5 themes related to the use of GeoGebra software in mathematics learning, namely: “control group”¸“concept”, “medium”, “subject”, “analysis”, and “ article” which is still rarely researched and is a theme in the renewal of research. This theme is used as reference material for further research.